2002
DOI: 10.1124/dmd.30.9.1005
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation of Dihydroartemisinin in Vivo and by Human Liver Microsomes and Expressed UDP-Glucuronosyltransferases

Abstract: ABSTRACT:The aim of this study was to elucidate the metabolic pathways for dihydroartemisinin (DHA), the active metabolite of the artemisinin derivative artesunate (ARTS). Urine was collected from 17 Vietnamese adults with falciparum malaria who had received 120 mg of ARTS i.v., and metabolites were analyzed by high-performance liquid chromatography-mass spectrometry (HPLC-MS). ) but not with UGT1A1 or UGT1A6. There was no significant metabolism of DHA by cytochrome-P450 oxidation or by cytosolic sulfotransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
105
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 34 publications
(30 reference statements)
0
105
0
Order By: Relevance
“…Artemisinin-based combination therapies, including those with DHA, are viewed as the most promising drug strategies for combating malaria-related morbidity and mortality [8,9]. In Vietnamese adult malaria patients given artesunate, α-DHA-β-glucuronide was found to be the major urinary product of DHA glucuronidation, and, using V79 cells expressing human UGT1A1, 1A6, 1A9, or 2B7, α-DHA-β-glucuronide formation was observed with UGT1A9 and UGT2B7, but not with UGT1A1 and UGT1A6 [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Artemisinin-based combination therapies, including those with DHA, are viewed as the most promising drug strategies for combating malaria-related morbidity and mortality [8,9]. In Vietnamese adult malaria patients given artesunate, α-DHA-β-glucuronide was found to be the major urinary product of DHA glucuronidation, and, using V79 cells expressing human UGT1A1, 1A6, 1A9, or 2B7, α-DHA-β-glucuronide formation was observed with UGT1A9 and UGT2B7, but not with UGT1A1 and UGT1A6 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Using HEK293 cells expressing human UGT2B4, 2B7, 2B10, 2B11, 2B15, or 2B17, it was observed that only UGT2B7 catalyzed the formation of AZT-glucuronide [10]. The DHA glucuronidation [4] and AZT glucuronidation [10] studies were not performed with all 18 known human UGTs, and it is possible that other UGTs might be important for the glucuronidation of these anti-infectious drugs. Although efavirenz and its phase I hydroxyl metabolites [11] and phase I hydroxyl metabolites of nevirapine [12] have been shown to undergo glucuronidation, indicating the involvement of phase II pathway through UGTs, there is currently no information, to our knowledge, on the identity of the UGT involved in the glucuronidation of these commonly prescribed antiretroviral drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, AS is known to be completely hydrolyzed in the blood by tissue cholinesterases to yield its active metabolite, DHA, 38 and DHA is further conjugated by the UDP-glucuronosyltransferase system. 39 In addition, AS has been reported to be metabolized by CYP450. In this regard, CYP2A6 has been found to be the major metabolizing enzyme for AS.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to AS, no notable change was observed in the pharmacokinetic parameters of DHA in DM rats, whereas the AUC of blood was slightly increased in DM (Figure 2 and Table 3). After its conversion from AS, DHA is not oxidized by cytochrome-P450, but is glucuronidated by the UDP-glucuronosyltransferases 1A9 and 2B7 (UGT1A9 and UGT2B7) in the liver [28,29]. Dostalek et al, investigated the effect of DM on glucuronidation by UGT1A9 and UGT2B7 in the human liver and showed that the expression and activity of UGT2B7, but not of UGT1A9, were significantly decreased in DM [30]; however, the effect of DM on DHA disposition was not significant in rats in the present study.…”
Section: Discussionmentioning
confidence: 99%